Unemployment in the Euro Area and Unconventional Monetary Policy Surprises - Oliver Hülsewig; Horst Rottmann (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine the impact of the European Central Bank's monetary policy on the euro area labor markets over the period 2010-2018. Using Jordà's (2005) local projection method, we find that unemployment rates decline in response to expansionary monetary policy surprises that can be related to unconventional policy measures. At the same time, hours worked rise. In the periphery countries, the reduction in unemployment rates is relatively pronounced, while in the core countries it is only minor. Thus, labor markets in the euro area were impacted differently by unconventional monetary policy measures.
Keywords: E24; E52; E58; C23; 330; Euro area; unconventional monetary policy; labor markets; local projections